A new species of Leurocephala Davis & Mc Kay (Lepidoptera, Gracillariidae) from the Azapa Valley, northern Chilean Atacama Desert, with notes on life-history - Pereira, Cristiano Marcondes (2017)
The Neotropical micromoth genus Leurocephala Davis & Mc Kay, 2011 (Lepidoptera, Gracillariidae) was originally described to include only the type species, L. schinusae Davis & Mc Kay, 2011, whose leaf miner larvae are associated with Anacardiaceae in Argentina, Brazil and Paraguay. An integrative analy- sis including morphology, life history and DNA barcode sequences revealed that specimens collected on Schinus molle L. (Anacardiaceae) in the coastal valleys of the Atacama Desert of northern Chile belong to a second species of this formerly monotypic genus. Adults of Leurocephala chilensis Vargas & Moreira sp. nov. are herein described and illustrated in association with the immature stages and life history, and corresponding phylogenetic relationships are assessed based on DNA barcode sequences. This finding provides the first record of Leurocephala from west of the Andes Range, expanding remarkably its geo- graphic range. It is suggested that the extent of diversity within Leurocephala is much greater and that variation in geographic factors and host plant use may have modeled it, an evolutionary hypothesis that should be assessed in further studies.